Test–Retest Reliability of the APTA Professionalism in Physical Therapy: Core Values Self-Assessment Tool in DPT Students. Issue 4 (December 2017) - Denton, Jason; Fike, David S.; Walk, Matt; Jackson, Chad
Abstract : Study Design: Test–retest reliability study. Introduction: Promoting professionalism is one of the key components of APTA's Vision 2020. The PTCVSA tool is used in PT educational programs as an assessment tool and to facilitate reflection. The tool is also in its initial use as a research tool with PTs. The psychometric properties of this tool have not been established. Methods: Participants completed the PTCVSA tool on two occasions using a test–retest design. A total of 96 PT students, including 50 first-year and 46 second-year students, completed both tests. Psychometric testing was undertaken, including internal consistency using Cronbach α and test–retest reliability. Results: Internal consistency (Cronbach α) of the individual core values ranged from .713 (accountability) to .934 (social responsibility). The test–retest reliability intraclass correlation coefficient (ICC) for the entire tool was .753 overall. Test–retest reliability was marginal (.625) in first-year students but was acceptable (.798) in second-year students. Intraclass correlation coefficient values for individual core values ranged from .538 (accountability) to .787 (social responsibility). Discussion: Although the PTCVSA may continue to be a valuable self-reflection tool for all students in PT education programs, it was not a reliable measurement tool in the first-year students participating in this study. Conclusion: In this preliminary investigation, the PTCVSA demonstrated acceptable reliability as a measurement tool for self-assessment of professional behaviors in second-year students who have been in a clinical experience.